HDAC1-3 inhibition triggers NEDD4-mediated CCR2 downregulation and attenuates immunosuppression in myeloid-derived suppressor cells - Zhiqi Xie; Jinjin Shao; Zeren Shen; Zhichao Ye; Yoshiaki Okada; Daisuke Okuzaki; Naoki Okada; Masashi Tachibana (Cancer Immunology, Immunotherapy)
Abstract Myeloid-derived suppressor cells (MDSCs) play a critical role in cancer progression and resistance, thus representing promising targets for immunotherapy. Despite the established role of histone deacetylases (HDACs) in epigenetic regulation of cell fate and function, their specific impact on MDSCs remains elusive. We sought to investigate the effects and underlying mechanisms of HDAC on MDSCs using various HDAC inhibitors. Our results indicate that HDAC1-3 inhibitors reduce CCR2 expression, a chemokine receptor that mediates the migration of monocytic (M-)MDSCs to tumors and attenuated the immunosuppressive activity of MDSCs. In an orthotropic hepatocellular carcinoma (HCC) murine model, HDAC1-3 inhibitors reduced the infiltration of M-MDSCs, increased the number of natural killer cells in tumors, and suppressed tumor growth. Our results also suggest that HDAC1-3 inhibitors potentiate the antitumor effects of anti-programmed cell death protein 1 antibodies. ATAC-seq and RNA-seq analyses revealed 115 genes epigenetically upregulated by HDAC1-3 inhibitors, primarily linked to transcriptional regulation and ubiquitination. We further elucidated that HDAC1-3 inhibitors facilitate CCR2 protein degradation through ubiquitination-mediated by NEDD4 E3 ligase. Our findings reveal a novel mechanism of action of HDAC1-3 inhibitors in MDSCs and suggest a potential synergistic immunotherapy strategy for clinical benefit in HCC.